Christmas after midnight [compact disc] - Fantasia, 1984-; Cee-Lo (Musician) (Concord Records, 2017)
Multi-platinum, Grammy award winning artist Fantasia releases her first ever holiday album featuring timeless classics in her own unique style, including The Christmas Song; Angels We Have Heard on High; Christmas Time is Here; and more.